SOSIALISASI KURIKULUM MERDEKA BELAJAR BAGI GURU-GURU DI SMP NEGERI 1 DOLOK PARDAMEAN - Apriani Sijabat; Herna Febrianty Sianipar; Christa Voni Roulina Sinaga; Ropinus Sidabutar; Mungkap Siahaan; Asima Rohana Sinaga; Rudiarman Purba (Universitas Galuh, 2022)
The independent learning curriculum has been implemented in various educational units in Indonesia. Facts on the ground state that not all stakeholders understand the free learning curriculum. Therefore, the service team of HKBP Nommensen Pematangsiantar University has carried out community service at SMP Negeri 1 Dolok Pardamean, Simalungun Regency, where this service aims to socialize the independent learning curriculum for teachers of SMP Negeri 1 Dolok Pardamean. This service received a good response and was appreciated by the Principal of SMP Negeri 1 Dolok Pardamean. The results obtained from this service were 76.7% of the participants stated that they were satisfied with this service. It is hoped that through this activity there will be cooperation between the university and the school to develop the quality of teachers for the creation of quality education.